PV Emulator - Pelin, Denis; Jelena Jukić Antolović; Rapčan, Vjekoslav (International Journal of Electrical and Computer Engineering Systems, 2014)
The photovoltaic emulator (PV emulator) described in the paper is used for laboratory exercises in the courses Renewable Energy Sources and Emergency/Standby Power Supply Systems in the Graduate (Master) Studies in Electrical Engineering – Power Systems Engineering and Principles of Power Electronics in the Undergraduate (Bachelor) Studies in Electrical Engineering as well as for scientific research relating to setting an optimal photovoltaic system for regional climatic elements. The paper gives a detailed description of subsystems of the PV emulator as well as a possibility of DC programmable sources of the subsystem. It is shown how electricity production from the photovoltaic system with peak power of up to 12 kW can be emulated by using the PV emulator for one chosen day in the month.